Mortar pore pressure prediction during the first hours of cement hydration. (May 2021) - Craipeau, Typhanie; Perrot, Arnaud; Toussaint, Fabrice; Huet, Bruno; Lecompte, Thibaut
Abstract: During cement hydration, solid, fluid, and total volumes vary as water is consumed by chemical reactions. Those volume variations lead to pore water pressure decrease during the first hours of hydration. The deformations induced by early hydration are quantified in order to understand their consequences on the internal stress state within the hardening material. This paper aims to link pore water pressure with autogenous and chemical shrinkage during the first hours of hydration in the bulk of early setting cement mortar. It is demonstrated that specific volume variations are compensated by an increase of air-entrained volume. The variation of the volume of air is used to predict the air pressure. Using the size of a maximum capillary pore diameter filled with water, the capillary pressure is estimated using the Young-Laplace equation. In order to validate the approach, the pore water pressure is measured and compared to the thermodynamic prediction and air content.